2017
DOI: 10.1016/j.jvs.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Timing and Type of Groin Wound Complications Highlights the Need for Uniform Reporting Standards

Abstract: Objective: Abdominal aortic aneurysm (AAA)-related mortality is decreasing since the introduction of endovascular aneurysm repair, but mortality from AAAs by age, sex, and race has not been recently reported.Methods: We abstracted crude mortality rates by International Classification of Diseases, Tenth Revision code from the Centers for Disease Control and Prevention Wonder database from 1999 to 2015 and stratified these by year, diagnosis, age, sex, race, and state.Results: We found that overall AAA-related m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…4 Audu et al (2019) reported groin complications after vascular surgery in 20.7% of patients during a 6 month follow-up period, ranging from minor infection treated with antibiotics as an outpatient, to major complications requiring re-admission and often surgery. 1 Wound dehiscence may be caused by a post-operative haematoma and dermal or fat necrosis. 5 Another problem is that of lymphatic leak (LL) following uncomplicated arterial revascularisation, which reportedly occurs in as many as 5% to 8% of all cases.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…4 Audu et al (2019) reported groin complications after vascular surgery in 20.7% of patients during a 6 month follow-up period, ranging from minor infection treated with antibiotics as an outpatient, to major complications requiring re-admission and often surgery. 1 Wound dehiscence may be caused by a post-operative haematoma and dermal or fat necrosis. 5 Another problem is that of lymphatic leak (LL) following uncomplicated arterial revascularisation, which reportedly occurs in as many as 5% to 8% of all cases.…”
Section: Introductionmentioning
confidence: 99%
“…Complications include surgical site infection, wound breakdown, and poor healing with risk to the integrity of any underlying graft. Management of such problems may require prolonged hospital stay, re‐admission, and surgical re‐intervention 1‐4 . Rates of groin wound complications vary in the literature depending on definitions and reporting standards.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of published literature regarding groin SSIs have been small, 28 from single centres, 10,11 historical, reliant on national registry data, 7,28 use varying definitions of SSI 29 and are retrospective. 28 This has made it difficult to benchmark practice and provide estimates to inform the design of future randomised trials.…”
Section: Discussionmentioning
confidence: 99%